School Lunch Take up and Attainment in Primary and Secondary Schools in England - Nelson, Michael; Gibson, Karen; Nicholas, Jo (Frontiers in Public Health, 2015)
Hypothesis Average levels of attainment in primary and secondary schools in England in 2010 and 2011 are positively associated with changes in average school lunch take up between 2008–2009 and 2010–2011. Subjects/methods Average school lunch take up and attainment data were available for 2009–2011 for primary and secondary sectors in a minimum of 106 local authorities (LAs) in England and 853 individual primary schools in six LAs. Associations between attainment at 11–12 years (primary) and 15–16 years (secondary) and changes in school lunch take up were tested using multilevel analysis, multiple regression, and cross-tabulation (chi-squared analysis). Results At school level, attainment at 11–12 years in 2010 and 2011 showed 9 positive and 12 negative associations with changes in school lunch take up between 2009 and 2011. At LA level, average attainment at 15–16 years in 2011 was associated with changes in total school lunch take up in 2010–2011 (p = 0.034). Cross-tabulation of changes in attainment 2010–2011 (above or below median) were positively associated with changes in total school lunch take up between 2009 and 2011, by quartiles (Chi-squared = 11.041, df = 3, p = 0.012). Conclusion Attainment at secondary level in England is statistically significantly associated with increases in healthier school lunch take up. Results in the primary sector are not consistent.